Data_Sheet_1_Prokaryotic Diversity and Composition of Sediments From Prydz Bay, the Antarctic Peninsula Region, and the Ross Sea, Southern Ocean.PDF - Jiang Li; Xiaoqian Gu; Yuanyuan Gui (2020)
The V3–V4 hypervariable regions of the 16S ribosomal RNA gene were analyzed to assess prokaryotic diversity and community compositions within 19 surface sediment samples collected from three different regions (depth: 250–3,548 m) of Prydz Bay, the Antarctic Peninsula region, and the Ross Sea. In our results, we characterized 1,079,709 clean tag sequences representing 43,227 operational taxonomic units (OTUs, 97% similarity). The prokaryotic community distribution exhibited obvious geographical differences, and the sequences formed three distinct clusters according to the samples’ origins. In general, the biodiversity of Prydz Bay was higher than those of the Antarctic Peninsula region and the Ross Sea, and there were similar prokaryotic communities in different geographic locations. The most dominant clades in the prokaryotic communities were Proteobacteria, Bacteroidetes, Thaumarchaeota, Oxyphotobacteria, Deinococcus-Thermus, Firmicutes, Acidobacteria, Fusobacteria, and Planctomycetes, but unique prokaryotic community compositions were found in each of the sampling regions. Our results also demonstrated that the prokaryotic diversity and community distribution were mainly influenced by geographical and physicochemical factors, such as Zn, V, Na, K, water depth, and especially geographical distance (longitude variation of sample location) and Ba ion content. Moreover, geochemical factors such as nutrient contents (TC, P, and Ca) also played important roles in prokaryotic diversity and community distribution. This represents the first report that Ba ion content has an obvious effect on prokaryotic diversity and community distribution in Southern Ocean sediments.